EFFECT OF BORON AND ETHEPHON IN GROWTH AND YIELD OF BREAD WHEAT - & Hashim, Al-Naqeeb (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The experiment was carried out at the farm of field of Crops Department, College of Agriculture, University of Baghdad during 2010-2011 and 2011-2012 seasons to study the effect of boron elements and ethephon on some growth characteristics and the yield of wheat (Triticum aestivum L.) Abu Ghraib-3 var. A split plot arrangement according to RCBD was used with four replications. The boron spray with three concentrations (50, 75 and 100) mg B.L-1 in addition to control treatment (without boron) as a main plots, and the second factor was soaking of wheat seed with concentrations level of ethephon (1500, 2500 and 3500) mg.L-1 in addition to control treatment (without soaking) as a sub plots. The results of showed that 100 mg B.L-1 gave highest means for plant height (108.81 and 115.53) cm, crop growth rate (32.80 and 35.30) gm.m-2. day-1, number of grains per spike (47.44 and 48.58) grain.spike-1, weight of 1000 grain (42.04 and 41.37) gm, grain yield (4.76 and 5.01)m ton.ha-1, biological yield (12.15 and 12.57) ton.ha-1, harvest index (39.19 and 39.89)%. In addition, the results showed that soak wheat seed with 3500 mg.L-1 caused significant decrease in height plant (93.98 and 101.66) cm and this treatment (3500 mg.L-1) gave highest means for number of tillers (505.29 and 519.06) tiller.m-2, crop growth rate (33.44 and 35.78) gm.m-2. day-1, number of spikes (384.61 and 415.55) spike.m-2, number of grains per spike (46.37 and 47.21) grain.spike-1, grain yield (4.67 and 4.85) ton.ha-1, biological yield (11.96 and 12.55) ton.ha-1 and harvest index (39.01 and 38.61)% for both seasons, respectively. The interaction between 100 mg B.L-1 and 3500 mg.L-1 ethephon gave highest mean for crop growth rate (35.76 and 38.83) gm.m-2. day-1 for both seasons, respectively.